2007
DOI: 10.7589/0090-3558-43.1.32
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Murid Gammaherpesvirus 4 Within Wild, Sympatric Populations of Bank Voles and Wood Mice

Abstract: ABSTRACT:Murid gammaherpesvirus 4 (MuHV-4) is widely used as a small animal model for understanding gammaherpesvirus infections in man. However, there have been no epidemiological studies of the virus in wild populations of small mammals. As MuHV-4 both infects cells associated with the respiratory and immune systems and attempts to evade immune control via various molecular mechanisms, infection may reduce immunocompetence with potentially serious fitness consequences for individuals. Here we report a longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 21 publications
(21 reference statements)
4
30
0
Order By: Relevance
“…A long-term study of MHV-68 antibodies in a mixed population of C. glareolus and A. sylvaticus in UK (Telfer et al 2007) revealed their higher prevalence in the latter host, thereby supporting a previous view that A. sylvaticus is the major natural host of MHV-68, even though this virus was originally isolated from C. glareolus. An investigation of incidence of 13 different viruses in Mus domesticus (Schwarz & Schwarz, 1943) in UK using serology (Becker et al 2007) showed for MHV-68 values of 3-13%.…”
Section: Introductionsupporting
confidence: 70%
“…A long-term study of MHV-68 antibodies in a mixed population of C. glareolus and A. sylvaticus in UK (Telfer et al 2007) revealed their higher prevalence in the latter host, thereby supporting a previous view that A. sylvaticus is the major natural host of MHV-68, even though this virus was originally isolated from C. glareolus. An investigation of incidence of 13 different viruses in Mus domesticus (Schwarz & Schwarz, 1943) in UK using serology (Becker et al 2007) showed for MHV-68 values of 3-13%.…”
Section: Introductionsupporting
confidence: 70%
“…This hypothesis was formed on the basis of the previous observation that latent herpesviruses have multiple stimulatory effects on the host immune system. 18,19 We tested this idea using Murid herpesvirus 4 (MuHV-4, also known as murine gammaherpesvirus-68), a natural pathogen in wild mice 20 that is closely related to the human viruses Kaposi sarcoma-associated herpesvirus and Epstein-Barr virus. MuHV-4, like all herpesviruses, establishes life-long latent infection (carriage of the viral genome in latently infected cells punctuated by intermittent reactivation) in its hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Viral DNA was detected by PCR in the lungs and less commonly in the spleen of these animals. Another study of specific antibodies in C. glareolus and A. sylvaticus in UK revealed their higher prevalence in the latter host (Telfer et al (2007), thereby supporting a generally accepted view that even though MHV-68 was originally isolated from C. glareolus, its major natural host is A. sylvaticus. A two-year study of the epidemiology of the virus infection in A. sylvaticus and C. glareolus by Knowles et al (2012) suggested that (i) male reproductive behaviours of these animals represnt an important natural route of transmission of this virus and (ii) this infection may have a detrimental effect on other wild hosts, thus objecting the view that gammaherpesviruses have limited impacts on natural co-evolved host species.…”
Section: Maintenance Of the Virus In Reservoir Animalsmentioning
confidence: 65%
“…One of relatively novel herpesviruses is also the murine gammaherpesvirus 68 (MHV-68) which was isolated from wild murid rodents in Slovakia (Blaškovič et al, 1980) and later in other European countries including UK (Blasdel et al, 2003;Telfer et al, 2007). The objective of this review was to cover the biology of MHV-68 and the role of individual animal hosts species in its maintenance and spread in the nature.…”
Section: Introductionmentioning
confidence: 99%